IPO of Ukrainian companies on the Warsaw Stock Exchange (WSE) - Kondrat, Iryna; Malets, Oksana (Lviv Polytechnic Publishing House, 2015)
The paper analyzes the Initial Public Offering of shares of Ukrainian companies on the Warsaw stock exchange. Also, it provides a comparative analysis of the composition and dynamics of the WIG-Ukraine and WIG-Poland indexes.
Keywords: Initial Public Offering; IPO; Warsaw Stock Exchange; GPW; index WIG-Ukraine; index WIG-Poland; capital; financial instruments; stock market; shares; investors